ANALISIS KESULITAN BELAJAR DAN PENCAPAIAN HASIL BELAJAR SISWA MELALUI STRATEGI PEMBELAJARAN INKUIRI - Izaak H. Wenno; Katerina Esomar; Venty Sopacua (LPMPP Universitas Negeri Yogyakarta, 2016)
Abstrak: Tujuan penelitian ini adalah untuk mengetahui kesulitan belajar dan pencapaian hasil belajar siswa SMA pada materi elastisitas bahan. Penelitian ini merupakan penelitian deskritif dengan sampel kelas XI IPA Negeri 5 Ambon. Data analisis kesulitan belajar diperoleh melalui angket, sedangkan data pencapaian hasil belajar diperoleh dari nilai formatif dan proses yang meliputi nilai kognitif, afektif, dan psikomotor. Data dianalisis dengan teknik statistik deskriptif. Hasil penelitian menunjukkan bahwa selama proses pembelajaran terdapat empat jenis kesulitan, yaitu kesulitan dalam menguasai konsep, mengaitkan hubungan antara konsep, menguasai rumus, dan mengoperasikan rumus saat menyelesaikan soal. Sebelum menggunakan strategi inkuiri, kemampuan siswa menguasai konsep antara 69,2-82,3%. Setelah penggunaan strategi inkuiri, kemampuan siswa meningkat menjadi 90,8%. Kemampuan mengaitkan antarkonsep meningkat menjadi 89,2%. Kemampuan menguasai rumus 87,1%, dan kemampuan mengoperasikan rumus untuk penyelesaian soal 91,3%. Peningkatan hasil belajar juga terjadi pada konsep elastisitas bahan. Strategi pembelajaran inkuri dapat mengatasi kesulitan belajar siswa 4 dan dapat mencapai hasil belajarnya pada materi elastisitas bahan. Kata Kunci: strategi pembelajaran inkuiri, kesulitan belajar, dan pencapaian hasil belajar ANALYSIS OF STUDENTS’ LEARNING DIFFICULTIES AND ACHIEVEMENT IN THE IMPLEMENTATION OF INQUIRY LEARNING Abstract: The purpose of this study is to revealstudents’ learning difficulties and achievement in learning the concepts of material elasticityin class XI SMA. This research belongs to descriptive study done to a sample of class XI IPA4 Negeri 5 Ambon with the total of 39 students. Learning difficultiesdata were obtained through questionnaires before and after the implementation of inquiry learning, while achievement data were obtained from the formative and process values that includes cognitive (student worksheet), affective, and psychomotor aspects duringthe learning activities. The results show that during the process of learning physics in particular on the concept of material elasticity, there are four types of difficulties experienced by students, i.e. difficulty in mastering the concepts, difficulty in establishing links betweenconcepts, difficulty in mastering formulas, and difficulty in operating formulas for solving problems. The results showthat students’ ability to master the concepts ranges 69.2 to 82.3% before applying the inquiry strategy and reaches 90.8% after using the strategy. The ability to link concepts increases to 89.2%. The ability to master the formula reaches 87.1%, and the ability to operate formulas for solving problemsis about 91.3%. The learning outcomes are also improving. Thus, it can be concluded that inqury learning strategies can address students’ learning difficulties and can help students achieve better results in learning material elasticity concept. Keywords: inquiry learning strategies, learning difficult, and learning outcomes